STRATEGI PENANAMAN NILAI AGAMA DAN MORAL PADA SEKOLAH BERBASIS AGAMA HINDU PADA ANAK USIA DINI - Maharani, Maharani; Kholifah, Siti Rodiatun (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2024)
Religious and moral values are important to instill early. This is done with the stages of early childhood development using fun methods because today learning only emphasizes on increasing intellect (IQ) so that it has implications for the spiritual dryness of human beings. This research uses learning strategies for early childhood and the importance of embedding religious and moral values for early childhood. This research uses qualitative descriptive research. Data is obtained from observation, interviews, and documentation. After the data is obtained, data reduction, data display, and conclusion will be carried out. Based on the data analysis that has been done, the researcher draws the conclusion that the learning strategy applied at Pradnya Paramita Kindergarten in instilling religious and moral values by: (1) student-centered learning, (2) play, (3) storytelling, (4) singing, (5) and integrated learning.